Presenting features of locally advanced breast cancer : a crosssectional study (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Worldwide, breast cancer is the most frequently diagnosed life-threatening cancer in women. This cross sectional study was done to assess the presenting features of locally advanced breast cancer. The mean age was 42.6 years with standard deviation 9.56, 86% were house wife, 53.5% were illiterate, 16% were postmenopausal and 75.8% had BMI of 20Kg/m2. Ninety one point five percent had menarche at or above 12 years of age and 26.6 % had history of using hormonal contraceptives. Tobacco user and positive family history were found in 21.2% and 5.35% of the cases. 84% were presented with only lump and 16% with both lump and ulceration. Right breast was involved in 51.1%. About 37% cases presented on 3rd month of their symptoms. Around 71.2% patients presented with lump >5cm in diameter, axillary lymph nodes were palpable in 81% and fixed in 31% of patients. Around Sixty three percent of patients were in stage IIIA. Still a large fraction of patients present with advanced stage with varied presentation, sometimes surgeons face difficulties to offer the treatment. Proper awareness, early presentation and early detection give them the opportunity to receive the best treatment.BSMMU J 2021; 14(4): 148-151